Słowo-obraz w przestrzeni. Poezja w projektach site-specific. Komentarz do twórczości Joana Brossy oraz Iana i Aleca Finlayów - Hołody, Miłosz; Krzosek-Hołody, Magdalena (Wydział Sztuki UR, 2018)
The article explores the role of visual poetry in site-specific projects. The authors analyze the contribution of avant-garde movements of the second half of the 20th century to the development of object-poems and their migration into the landscape and public space. They focus on the heritage of futurism, land art. and contextual art. The paper presents classic works of Ian Hamilton Finlay and Joan Brossa as well as recent projects by Alec Finlay.
Word-image in space. Poetry in site-specific projects. A commentary on the work of Joan Brossa and Ian and Alec Finlays
Keywords: poezja; poezja wizualna; sztuka site-specific; sztuka środowiskowa; poetry; visual poetry; site-specific art; environmental art